Bildende Kunst in Bonn 1945-1952. (Bonn : Städtisches Kunstmuseum, 1985)
Bretz, Julius ; Nonn, Carl ; Frey, Martin ; Mense, Carlo ; Jansen, Franz M. ; Coenen, Otto ; Magar, Paul ; Stucke, Willy M. : Dienz, Herm ; Dotterweich, Juan ; Felicitas Auer, Magda ; Fassbender, Joseph ; Berke, Hubert ; Trier, Hann ; Schoneweg, Walter ; van Ackeren, Carl ; von Rath, Ingeborg ; Berges, Hermann
Bildende Kunst in Bonn 1945-1952, Städtisches Kunstmuseum, Bonn, 16. Okt. - 8 Dez. 1985
boek
Keywords: Bonn